Inhibition monitoring in veterinary molecular testing - Yan, Lifang (J Vet Diagn Invest, 2019)
Many of the sample matrices typically used for veterinary molecular testing contain inhibitory factors that can potentially reduce analytic sensitivity or produce false-negative results by masking the signal produced by the nucleic acid target. Inclusion of internal controls in PCR-based assays is a valuable strategy not only for monitoring for PCR inhibitors, but also for monitoring nucleic acid extraction efficiency, and for identifying technology errors that may interfere with the ability of an assay to detect the intended target. The Laboratory Technology Committee of the American Association of Veterinary Laboratory Diagnosticians reviewed the different types of internal controls related to monitoring inhibition of PCR-based assays, and provides information here to encourage veterinary diagnostic laboratories to incorporate PCR internal control strategies as a routine quality management component of their molecular testing.